Development of energy efficiency controller using PIC 16F877A: article / Mohamed Al-Hafiz Zainuddin - Zainuddin, Mohamed Al-Hafiz (2010)
The word 'forgot9 is seems to be a nature habit to human. The main purpose of this project is to develop energy efficiency controller to control electrical energy used by user efficiently. Sometimes, people do not aware to switch off the equipments such as light and air-conditioner before they leave their room. The concept of this project is to switch off the air-conditioner and lights when there are no users in the room and switch on the device automatically when a person enter the room. The system interface is using the peripheral interface controller (PIC) 16F877A for the sensor automation concept of the system. From the data collection, there are several assumptions been made such as calculation of current usage for air-conditioner at a classroom. The initial result of the energy efficiency controlled showed it can improve the efficiency of the energy.